1977
DOI: 10.1507/endocrj1954.24.251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vagotomy on hyperinsulinemia in obese rats with hypothalamic lesions.

Abstract: SynopsisWith the purpose of investigating the pathogenesis of obesity and hyperinsulinemia in rats with hypothalamic lesions (HTL), HTL were made in vagotomized rats, and the development of obesity was serially followed In order to elucidate the cause of obesity, we have studied the pathogenesis of obesity in rats with hypothalamic lesions (HTL) and the following results have been reported previously.1. Rats with HTL have a tendency of hyperphagia from the early stage afer HTL and become markedly obese. 2. Fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…The observation that hypothalamic obesity could not be produced in rats in which B cells had been destroyed by streptozotocin administration and replaced by fetal pancreas transplants devoid of intact innervation (16), supported the concept of a direct neural influence on the B-cell function. Analogous conclusions were drawn on the basis of chronic experiments carried out in VMHlesioned rats with superimposed vagotomy (17)(18)(19) creas (21)(22)(23). Thus, based on the hypothesis of a vagally-mediated hyperinsulinemia in VMH-lesioned animals, one would anticipate changes not only in insulin secretion but in glucagon secretion as well.…”
Section: Introductionmentioning
confidence: 76%
“…The observation that hypothalamic obesity could not be produced in rats in which B cells had been destroyed by streptozotocin administration and replaced by fetal pancreas transplants devoid of intact innervation (16), supported the concept of a direct neural influence on the B-cell function. Analogous conclusions were drawn on the basis of chronic experiments carried out in VMHlesioned rats with superimposed vagotomy (17)(18)(19) creas (21)(22)(23). Thus, based on the hypothesis of a vagally-mediated hyperinsulinemia in VMH-lesioned animals, one would anticipate changes not only in insulin secretion but in glucagon secretion as well.…”
Section: Introductionmentioning
confidence: 76%
“…Lastly, VMH lesions in weanling rats do not induce hyperphagia but still result in HI and accumulation of fat [55]. Multiple groups noted a direct correlation between the change in body weight and the degree of HI following VMH lesion [56, 57]. Pharmacological reduction of insulin alleviates the hyperphagia and weight gain in multiple species [58, 59].…”
Section: How Does Hi Cause Obesity?mentioning
confidence: 99%
“…Following the initial report of Powley and Opsahl [24] that subdiaphragmatic vagotomy completely abolishes VMH obesity, a number of studies have obtained mixed results. Most experiments report that vagotomy either before or after VMH lesions or knife cuts prevents overeating and obesity [10,18,24,26], but other studies have reported that vagotomy had only a partial or no effect on the hyperphagia syndrome [9,20,36]. Furthermore, in those cases in which vagotomy blocked VMH hyperphagia, some investigators have argued that this is a result of the eating difficulties (dysphagia) produced by the surgery [8,18,20,36], while others contend that vagotomy specifically interferes with the neuroendocrine events responsible for the hyperphagia syndrome [19,24,25].…”
Section: Hyperphagia and Vagotomymentioning
confidence: 99%